2008
DOI: 10.1186/1743-422x-5-1
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent infections by all four dengue virus serotypes during an outbreak of dengue in 2006 in Delhi, India

Abstract: Background: Co-circulation of multiple dengue virus serotypes has been reported from many parts of the world including India, however concurrent infection with more than one serotype of dengue viruses in the same individual is rarely documented. An outbreak of dengue hemorrhagic fever/dengue shock syndrome (DHF/DSS) occurred in and around Delhi in 2006. This is the first report from India with high percentage of concurrent infections with different dengue virus serotypes circulating during one outbreak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
196
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 251 publications
(219 citation statements)
references
References 23 publications
20
196
3
Order By: Relevance
“…Concurrent infection with the two different serotypes, DENV-1 and DENV-2, was identified in 43% of the samples in the present study. Similarly 43% co-infection was reported from Davangere, Karnataka [5] and 57% from Thiruvananthapuram, Kerala [6], 32·5% from Moreh, Manipur [38] and 19% from Delhi [3]. Our earlier work reported 9% co-infections during 2011 [7], 14% during 2013 [2] and 18% during 4 years of study from 2011-14 [39] in Delhi.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Concurrent infection with the two different serotypes, DENV-1 and DENV-2, was identified in 43% of the samples in the present study. Similarly 43% co-infection was reported from Davangere, Karnataka [5] and 57% from Thiruvananthapuram, Kerala [6], 32·5% from Moreh, Manipur [38] and 19% from Delhi [3]. Our earlier work reported 9% co-infections during 2011 [7], 14% during 2013 [2] and 18% during 4 years of study from 2011-14 [39] in Delhi.…”
Section: Discussionsupporting
confidence: 63%
“…Mean days of illness in co-infected patients was 3·80 (±1·72) days. The platelet count of the coinfected patients ranged from 0·6 to 3·5 lac/mm 3 . Three patients showed severe disease with mild haemorrhagic tendencies.…”
Section: Characteristics Of Co-infected Vs Mono-infected Patientsmentioning
confidence: 98%
See 2 more Smart Citations
“…The major serotype reported from PGI, Chandigarh during the outbreak in the year 2007 was serotype-1, but in 2005 it was serotype-2 [11]. A study from Delhi had reported concurrent prevalence of all the serotypes during 2008 [19]. Major dengue epidemics have been observed in the Indian subcontinent since the 1980s & researchers from the Pune-based NIV found that Indian DENV-2 strains isolated from 1956 to 2005 belonged to only two of the six genotypesAmerican and Cosmopolitan [20].…”
mentioning
confidence: 99%